Capacitorless one-transistor dynamic random access memory based on double-gate GaAs junctionless transistor. (24th April 2017) - Yoon, Young Jun; Seo, Jae Hwa; Cho, Min Su; Kim, Bo Gyeong; Lee, Sang Hyuk; Kang, In Man
Abstract: In this paper, we present a capacitorless one-transistor dynamic random access memory (1T-DRAM) based on a double-gate GaAs junctionless transistor (JLT). The proposed 1T-DRAM exhibits an excellent reading operation with a large sensing margin between the "1" and "0" states because the excess hole charges effectively screen the electric field formed by the gate2 voltage ( V GS2 ). In order to reduce the electric field in the drain–gate interface involved in recombination, HfO2 is used as the spacer dielectric. The 1T-DRAM obtains a long retention time of 71 ms due to a low recombination rate. Moreover, we investigate the effect of geometric parameters on DRAM characteristics. The gate length ( L G ) and body thickness ( T body ) have a major impact on the sensing margin and retention time. The 1T-DRAM with a long L G and a thin T body can operate with a low power (LP) consumption, a long retention time, and high-density integration.